What is the role of civil society in multisectoral nutrition governance systems? A multicountry review - Busse, H.; Covic, Namukolo M.; Jogo, W.; Aakesson, A. (SAGE Publications, 2020)
Objectives: To review attributes of civic engagement in multisectoral nutrition governance systems and to provide recommendations to increase CSO participation. Methods: We reviewed 7 national case studies of Civil Society Networks involved with the Scaling Up Nutrition movement and characterized 6 functional attributes of CSOs in multisectoral nutrition governance: identify needs of all community members, mobilize and build civic capacity, advocate for political commitments, inform program design and evaluation, ensure accountability mechanisms in public institutions, and report challenges and successes using broad media campaigns. Results: All studies described government agencies involved with multisectoral nutrition governance systems, at national and subnational levels; however, there was limited evidence of subnational platforms for CSO engagement. Although countries increased investments in public institutions for nutrition, it was unclear whether nutrition service quality improved and none reported corresponding investments in civil society.